2015
DOI: 10.1039/c5ce00767d
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures, and properties of nine d10or p-block coordination polymers based on a ligand containing both terpyridyl and sulfo groups

Abstract: Nine new coordination compounds, namely, {[Zn(HDSPTP) 2 (H 2 O) 4 ]·6H 2 O} n (H 2 DSPTP = 4'-(2,4disulfophenyl)-4,2':6'4''-terpyridine, 1), [Cd(DSPTP)(H 2 O) 2 ] n (2), {[Ag(HDSPTP)]·30H 2 O } n (3), 10 {[Ag(HDSPTP)(H 2 O)]·3H 2 O} n (4), [Ag 2 (DSPTP)] n (5), {[Ag 4 (DSPTP) 2 (H 2 O) 3 ]·2H 2 O} n (6), [Pb(DSPTP)(H 2 O) 2 ] n (7), {[Pb(DSPTP)(H 2 O) 3 ]·3H 2 O} n (8), and [PbK(DSPTP)(NO 3 )(H 2 O) 2 ]·H 2 O} n (9), were synthesized by introducing a ligand with both terpyridyl and sulfo groups as organic link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…For the divergent 4,2′:6′,4″-tpy, [Cd( 52 )(OH 2 ) 2 ] n (H 2 52 is defined in Figure 35 ) is a sole example of a cadmium(II)-containing coordination polymer with a sulfonato-functionalized 4,2′:6′,4″-tpy ligand for which structural data are available. Two independent reports of the synthesis and structure of [Cd( 52 )(OH 2 ) 2 ] n appeared in 2015 [ 95 , 96 ]. The compound was prepared under hydrothermal conditions from H 2 52 and either CdCO 3 or CdCl 2 ·2.5H 2 O, and crystallizes in the triclinic space group P –1.…”
Section: 42′:6′4″-terpyridinementioning
confidence: 99%
See 1 more Smart Citation
“…For the divergent 4,2′:6′,4″-tpy, [Cd( 52 )(OH 2 ) 2 ] n (H 2 52 is defined in Figure 35 ) is a sole example of a cadmium(II)-containing coordination polymer with a sulfonato-functionalized 4,2′:6′,4″-tpy ligand for which structural data are available. Two independent reports of the synthesis and structure of [Cd( 52 )(OH 2 ) 2 ] n appeared in 2015 [ 95 , 96 ]. The compound was prepared under hydrothermal conditions from H 2 52 and either CdCO 3 or CdCl 2 ·2.5H 2 O, and crystallizes in the triclinic space group P –1.…”
Section: 42′:6′4″-terpyridinementioning
confidence: 99%
“…The large voids in a single net result in 2-fold interpenetration ( Figure 35 b). Interestingly, when zinc(II) acetate combined with H 2 52 under the same hydrothermal conditions as for the preparation of [Cd( 52 )(OH 2 ) 2 ] n , single crystals of the mononuclear complex [Zn(H 52 ) 2 (OH 2 ) 4 ]·6H 2 O were obtained and PXRD data confirmed that the single crystal was representative of the bulk material [ 95 ]. The preference for mononuclear over polymeric assembly is not readily explained.…”
Section: 42′:6′4″-terpyridinementioning
confidence: 99%
“…According to the research of Zhao et al , 44 copper ions can promote the single electron transfer of electron-rich organic molecules and effectively mediate the oxidative-coupling reaction. Considering the coordinated group, the sulfonic acid group is a weaker electron donor compared with the carboxyl group and water molecule, 45 and the copper coordinated with the oxygen of the sulfonic acid group tends to require electrons from outside. In other words, in the catalytic reaction of oxidizing phenols, copper prefers to obtain electrons from phenols, which facilitates the catalytic reaction and thus leads to higher catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the widespread use of pyridinyl [5][6][7] and carboxylate [8][9][10][11][12][13] functionalities, sulfonate donors have also been used to access 3D frameworks. 14 3D-networks utilizing only the two pendant donors of the 4,2′:6′,4″-tpy domain are relatively rare, although the reaction of 4′-(pyridin-2-yl)-4,2′:6′,4″-tpy and CoIJNCS) 2 gives a 3D structure in which the pyridinyl substituent is not coordinated. 15 This is an unusual case where combination of a simple 4,2′:6′,4″-tpy ligand and Co(NCS) 2 leads to a 3D framework; more usually, 2D (4,4) or (6,3) nets result.…”
mentioning
confidence: 99%